(untitled) (International Journal of Biomedical Research, 2015)
Introduction: One of the challenges to maintain an agenda for universal coverage and equitable health system is to develop effective structuring and management of health financing. Global experiences with different systems of health financing suggest that a strong public role in health financing is essential for health systems to protect the poor. Health systems with the strongest state role are likely to be more equitable and achieve better aggregate health outcomes. Using Kenya as a case study, this paper seeks to evaluate the progress and capacity of a middle income country in terms of health financing for universal coverage, and also to highlight some of the key underlying health systems challenges. Methodology: The World Health Report 2010: Health Systems Financing: The Path to Universal Coverage was used as the framework to evaluate the Kenyan healthcare financing system in terms of the provision of universal coverage for the population, and the Kenyan National Health Sector Services Fund Accounts (2011) provided the latest Kenyan data on health spending. Measuring against the four target indicators outlined, Kenya fared modestly with total health expenditure close to 4.5% of its GDP (3.75%), out-of-pocket payment below 40% of total health expenditure (30.7%), comprehensive social safety nets for vulnerable populations, and a tax-based financing system that fundamentally poses as a national risk-pooled scheme for the population. Results: Nonetheless, within a holistic systems framework, the financing component interacts synergistically with other health system spheres. In Kenya, out-migration from public to private of public health workers particularly specialist doctors remains an issue and financing strategies needs to incorporate a comprehensive workforce compensation strategy to improve the health workforce skill mix. Health expenditure information is systematically collated, but feedback from the private sector remains a challenge. Conclusion: As far as Service delivery is concerned, there is a need to enhance financing capacity to expand preventive care, in better managing escalating healthcare costs associated with the increasing trend of non-communicable diseases. Additionally, health financing policies need to instill the element of cost-effectiveness to better manage the purchasing of new medical supplies and equipment. Good governance and leadership are needed to ensure adequate public spending on health and maintain the focus on the attainment of universal coverage, as well as making healthcare financing more accountable to the public, particularly in regards to inefficiencies and better utilization of public funds and resources.